Efficiency of Different Organic Surfactants on Nitrate Adsorption in Water: A Review - Mohsenipour1, Morteza; Shahid1, Shamsuddin; Ebrahimi2, Kumars; Alamgir1, Mahiuddin (Asian Journal of Chemistry, 2014)
Organoclays are modified clays in which the natural inorganic interlayer cations are replaced by organic cations. The net amount of organic cations adsorbed to the clay can exceed the cation exchange capacity of the clay, thus providing binding sites for exchangeable anions. Therefore, organic surfactants are efficient in the treatment of contaminated water. Here a review has been carried out to understand the efficiency of various organic surfactants, viz. hexadecyl trimethylammonium, hexadecyl pyridinium and benzethonium on nitrate reduction in drinking water. This study revealed that hexadecyl pyridinium are more efficient to remove nitrate in drinking water than other organic surfactants.